Analysis and geometry : MIMS-GGTM, Tunis, Tunisia, March 2014 ; in honour of Mohammed Salah Baouendi /: MIMS-GGTM, Tunis, Tunisia, March 2014 ; in honour of Mohammed Salah Baouendi. (2015) - Unknown
No abstract available